Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Motivasi dan Hasil Belajar IPS Materi Manusia, Tempat, dan Lingkungan Pada Siswa Kelas VII G SMP Negeri 1 Adiwerna Tahun Pelajaran 2019 / 2020 - M. Rochman Witono (Universitas Pancasakti Tegal, 2021)
Various problems that inform a teacher in the classroom are indicators that the learning motivation of studentswho receive the subject matter. If learning motivation is low, it will lead to low student learning outcomesbecause motivation is a determination and effort as a result of the interaction of the learning given by theteacher. The research objective was to increase learning motivation and improve social studies learningoutcomes. The steps in the research through cycle I and cycle II include planning, implementing actions,monitoring and reflecting. The results showed that the application of the Jigsaw cooperative learning modelcould increase the social studies learning motivation from 68.75% in the first cycle to 78.13% in the secondcycle. The application of the Jigsaw cooperative learning model could improve learning o utcomes in theclassical social studies subject from 81.25% in the first cycle to 87.50% in the second cycle. Based on all theresults of the research,